Highly Efficient Orange and Red Phosphorescent Organic Light‐Emitting Diodes with Low Roll‐Off of Efficiency using a Novel Thermally Activated Delayed Fluorescence Material as Host. (28th May 2015) - Wang, Hui; Meng, Lingqiang; Shen, Xingxing; Wei, Xiaofang; Zheng, Xiuli; Lv, Xiaopeng; Yi, Yuanping; Wang, Ying; Wang, Pengfei
<x xml:space="preserve">Abstract</x> MTXSFCz with thermally activated delayed fluorescence is synthesized. Orange and red phosphorescent organic light‐emitting diodes (PHOLEDs) with low efficiency roll‐off exhibit external quantum efficiencies (EQE) up to 11.8% and 15.6%. The efficient upconversion from triplet to singlet of the host reduces the triplet density and thus affords a low efficiency roll‐off of PHOLEDs.